(untitled) (The Review of Diabetic Studies, 2025)
Hyperpigmentation is a dermatological condition marked by localized overproduction of melanin, often associated with exposure to ultra violet rays, hormonal fluctuations, inflammation, or genetic predisposition. The present study was designed to investigate the anti-hyperpigmentation potential of phytochemicals derived from the methanolic extracts of Azadirachta indica, Aloe barbadensis miller, Punica granatum and Murraya koeingii using GC-MS analysis. A total of 206, 81, 177 and 7 compounds were identified from these plants respectively. Structural information of the identified compounds was retrieved from the PubChem database and pharmacokinetic profiling was conducted using SwissADME. Only compounds satisfying drug-likeness rules and exhibiting favourable skin permeation (log Kp) values were selected for docking studies. A total of 50 compounds passed all the drug-likeness tests of which 14 compounds exhibited good skin permeability. Molecular docking was employed to evaluate the interaction of these 14 phytocompounds using AutoDock with two key protein targets involved in melanogenesis: D-dopachrome tautomerase (PDB ID: 3KAN) and human tyrosinase-related protein 1 (PDB ID: 5M8L). Binding interactions were visualized and analyzed using Biovia Discovery Studio 2024. Two compounds 2,6,10-trimethylundeca-1,3-diene and oxalic acid, cyclobutyl tetradecyl ester exhibited the highest binding affinities against both protein targets, surpassing the docking performance of Thiamidol, a positive drug control. These findings highlight the potential of these naturally occurring compounds as effective inhibitors of melanin synthesis and safer, plant-based alternatives for hyperpigmentation therapy.